Neck muscle vibration produces diverse responses in balance and gait speed between individuals with and without neck pain - Nipaporn Wannaprom (2018)
© 2018 Elsevier Ltd Background: Neck muscle vibration can influence cervical proprioception and sensorimotor function. It is hypothesized to affect motor performance differently in persons with and without neck pain. Study design: Cross-sectional study. Objective: To clarify the extent to which vibration-induced motor responses of neck muscles affect static standing balance and gait speed in persons with and without neck pain. Methods: Thirty participants with chronic neck pain and 30 healthy controls were recruited. Balance and gait were measured before and after 30 s of suboccipital neck muscle vibration. Balance was measured in a confortable stance with eyes closed using a swaymeter and gait using the timed 10 m walk test. Results: At baseline, neck pain participants had greater postural sway, particularly in the anterior-posterior direction and slower gait speed than healthy controls (p < 0.001). Immediately after vibration, neck pain participants displayed decreased postural sway, and increased gait speed (p < 0.001). Healthy controls had increased postural sway and decreased gait speed (p < 0.001). Conclusion: Neck muscle vibration improved standing balance and gait speed in participants with neck pain but reduced performance in healthy controls. The study supports the importance of cervical proprioceptive information in postural control. Use of vibration could be considered neck pain patients' rehabilitation.